OFFERINGS DANCE AS A MEDIUM OF SOCIALIZING RELIGIOUS VALUES IN THE CATHOLIC CHURCH, GANJURAN, YOGYAKARTA - Pesulima, Merry Violyta Fransisca (The journal of contemporary issues in business and government, 2021)
The offering dance also known as standard dance is a religious or ritual ceremony comprising freedom of creation. Therefore, this study aims to identify the offering dance as a means of socializing religious values in the Catholic Church, Ganjuran, Yogyakarta. This is a qualitative research with anthropological and art approaches. Data were collected through observation, interviews, and documents. The obtained data were analyzed through data reduction, presentation, and verification procedures. Furthermore, the triangulation of data sources, methods, and theories was used to determine their validity. The values of religiosity associated with offering dance used the Bouman’s analysis to determine the values considered sacred by the community. These values are used as guidelines and further analyzed based on Maclever’s socialization analysis, which is a process that individuals go through to learn the norms, values, roles, and all other requirements needed to enable effective participation in social life. The results showed that the offering dance used as a means of socialization comprises educational, tolerance, moral education, culture, aesthetics, and social solidarity values. In addition, the findings also showed that the offering dance has been passed down from generation to generation with symbols capable of indirectly affecting the condition of the congregation and society.